Comparison of Reinforcement Waste of Columns and Beams in the Ditsamapta Building North Sumatra Regional Police Using Conventional Method and COP - Kevin Ghozali; Nur Wahid Btr, Agung; Rhini Wulan Dary (LPPM Politeknik Aceh Selatan, 2026)
Material is one of the most important resources in construction projects, contributing 40–60% of the total cost. Reinforcing steel often leaves excess material due to cutting errors, so optimization is needed to minimize waste. This study aims to compare waste calculation using the conventional method and Cutting Optimization Pro (COP) software through a bar bending schedule. The results show that the conventional method produced waste of Ø8 14.102%, Ø10 9.480%, D10 8.385%, D12 10.444%, and D16 9.500%. With COP, the waste decreased to Ø8 2.888%, Ø10 1.855%, D10 8.087%, D12 6.980%, and D16 5.756%. Overall, the use of COP was able to reduce waste by about 5% compared to the conventional method.